Beyond Environmental Law : Policy Proposals for a Better Environmental Future - Flournoy, Alyson C.; Driesen, David M. (Cambridge : Cambridge University Press, 2010)
This book offers a vision for the third generation of environmental law designed to enhance its ability to protect our environment. The book presents two core proposals, an Environmental Legacy Act to preserve a defined environmental legacy for future generations and an Environmental Competition Statute to spark movement to new clean technologies. The first proposal would require, for the first time, that the federal government define an environmental legacy that it must preserve for future generations. The second would establish a market competition to maximize environmental protection. The balance of the book provides complementary proposals and analysis. The first generation of environmental law sought broad protection of health and the environment in a fairly fragmented way. The second sought to enhance environmental law's efficiency through cost-benefit analysis and market mechanisms. These proposals seek to create a broader, more creative approach to solving environmental problems.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).